Monitoreo ambiental con detectores termoluminiscentes en Costa Rica - Mora Rodríguez, Patricia (Universidad de Costa Rica, 2009)
Using thermoluminiscent dosimeters (Harshaw TLD-200) the first set of Costa Rica data on absorbed doses in air from natural radiation is obtained. During the period September 1996 through October 2000 eight different sites throughout the country were chosen to install the TLD stations. Each station had 8 cards (five were changed every 3 months and 3 were changed annually). The dosimeters were read in the Atomic, Nuclear and Molecular Research Center using a 4000 Harshaw reader. Through a mathematical algorithm and its calibration factors the absorbed dose rate in air (nGy. h-1) was calculated. The national average is 108.9 ± 32.4 nGy.h-1, the lowest values (in nGy.h-1) were obtained at sea level at Quebrada Honda with 53 ± 11 and the highest values (in nGy.h-1) at Cartago with 160 ± 19. A slight increase with altitude is observed even though the Cartago station was always the highest. The values found agree with values reported worldwide.